Effectiveness of glucocorticoids use in patients with SARS-COV-2 - Marakushyn, Dmytro; Chernobay, Larysa; Isaieva, Inna; Karmazina, Iryna; Kosai, Zoabi (My University, 2020)
The purpose of our research was to summarize the current evidence of the effectiveness of glucocorticoid therapy for patients with SARS-COV-2. In our review, we have mentioned the principal mechanisms of corticosteroids action and their roles in suppression of immune response in patients with COVID-19. The research was done using available sources including). 15 were chosen concerning the topic of research. In conclusion, glucocorticoid therapy may increase the risk of death in patients with coronavirus infections who have mild symptoms but still no association found between glucocorticoids and mortality in patients with severe symptoms.Based on the data of researches, short-term and low dose systemic glucocorticoid therapy may be acceptable. But a step forward should be represented by the results of the researched, showing a reduction of death risk for patients on ventilators and on oxygen therapy treated with low dose of glucocorticoids. Currently, the use of immunosuppressants is considered reasonable, despite the risk of adverse events and delayed viral clearance, where the resolution of respiratory failure is the biggest problem in phases IIb and III of COVID-19 patients with the lack of drugs to be effective in such patients.
Keywords: COVID-19; glucocorticoids therapy; SARS-CoV-2; ARDS; immune response